2003
DOI: 10.1002/uog.903
|View full text |Cite
|
Sign up to set email alerts
|

Ear length in trisomy 21 fetuses at 11–14 weeks of gestation

Abstract: Objective To determine the value of measuring fetal ear length at 11-14 weeks of gestation in screening for chromosomal defects. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
1
13
0
2
Order By: Relevance
“…Shorter fetal ear length has been associated with aneuploidy and trisomy 21. 19,20 Commissural length was the only craniofacial parameter in the current study to vary significantly according to sex, with the distance being greater in male than in female newborns (2.74 vs 2.59 cm respectively). This finding is not supported by a study of North Indian newborns, which reported lengths of 2.49 cm and 2.45 cm for males and females respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Shorter fetal ear length has been associated with aneuploidy and trisomy 21. 19,20 Commissural length was the only craniofacial parameter in the current study to vary significantly according to sex, with the distance being greater in male than in female newborns (2.74 vs 2.59 cm respectively). This finding is not supported by a study of North Indian newborns, which reported lengths of 2.49 cm and 2.45 cm for males and females respectively.…”
Section: Discussionmentioning
confidence: 57%
“…In particular, this modality has been helpful in evaluation of facial abnormalities, hand abnormalities, club feet, skeletal dysplasia, and spinal malformations [1215]. To the best of our knowledge, there are only a few reports on the diagnosis of external ear abnormalities by ultrasonography which mainly focus on auricular deformities indicative of chromosomal abnormalities [4, 1618]. The aim of our study was to investigate the best time of examination and section chosen of routine prenatal ultrasound screening for fetal auricular abnormalities and evaluate the feasibility of examining the fetal ears with ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Newborns and adults with Down syndrome have short ears [37] , and prenatal studies showed a statistically significant difference between the ear sizes of normal fetuses and fetuses with trisomy 21 but only with a small degree of deviation from normal [38][39][40] . Probably due to this tiny difference, small ears were the only craniofacial feature not significantly different between Down syndrome and control fetuses in our study.…”
Section: Discussionmentioning
confidence: 99%